Peptide-based matrices as drug delivery vehicles. - Ezzat, K; Andaloussi, S; Abdo, R; Langel, U (2010)
Peptides, polypeptides and proteins have been extensively studied for their various structural and functional roles in living organisms. However, breakthrough discoveries in the last decades identified some peptide-based matrices that posses the ability to traverse biological membranes, and many peptides, polypeptides and even complete proteins have been shown to have such properties. Hence, these matrices have been successfully used for the intracellular delivery of many therapeutic cargos including small molecules, proteins, peptides, oligonucleutides, plasmids and nanoparticles both in vitro and in vivo. Being neither toxic nor carcinogenic and meanwhile efficient in delivery, they are recognized as very promising vectors to overcome the shortcomings of the available technologies. The characteristics of these peptide-based matrices and their applications in drug delivery are here briefly illustrated together with current challenges and future prospects.